2004
DOI: 10.1002/jnr.20058
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of α‐synuclein decreased viability and enhanced sensitivity to prostaglandin E2, hydrogen peroxide, and a nitric oxide donor in differentiated neuroblastoma cells

Abstract: Increased accumulation of alpha-synuclein is associated with certain neurodegenerative diseases including Parkinson's disease (PD) and Alzheimer's disease (AD). One mechanism of alpha-synuclein-induced toxicity involves increased oxidative stress. It was unknown whether neurons overexpressing alpha-synuclein would exhibit increased sensitivity to hydrogen peroxide (H(2)O(2)) or 3-morpholinosydnonimine (SIN-1; a nitrous oxide donor). To study this, we developed a murine neuroblastoma (NB) cell line that overexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…ONOO - and H 2 O 2 can each inhibit proteasomal activity, which in AD can cause APP accumulation and potentiation of OS and Aβ formation (Prasad et al, 2004). Further, 4-HNE affects proteasomal degradation by covalently adducting to cathepsin B, an integral protein in the degradation pathway (Crabb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…ONOO - and H 2 O 2 can each inhibit proteasomal activity, which in AD can cause APP accumulation and potentiation of OS and Aβ formation (Prasad et al, 2004). Further, 4-HNE affects proteasomal degradation by covalently adducting to cathepsin B, an integral protein in the degradation pathway (Crabb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…5 Although the majority of PD cases are sporadic, several studies have reported familial forms of the disease caused by point mutations [27][28][29] and multiplications 30,31 in genes that encode for proteins such as alpha-synuclein, parkin, 32 and DJ-1 33 that lead to nigrostriatal DA neurons degeneration and death, formation of protein aggregates, functional impairments of the ubiquitin-proteasome system, 34 mitochondrial dysfunction, 35 and oxidative stress. 36 Alpha-synuclein, a 14 kDa protein expressed in the presynaptic terminals of neurons, participates in synaptic vesicle recycling and dopaminergic neurotransmission. 37 The discovery that alpha-synuclein protein is a major component of Lewy bodies and Lewy neuritis in PD and that mutated alpha-synuclein has a tendency to misfold and aggregate, indicate that alpha-synuclein is a key element in the development of PD.…”
Section: Oxidative Stress In Pdmentioning
confidence: 99%
“…cDNA synthesis was carried out as previously described using 2 g total RNA [35]. Real time PCR was performed using LightCycler FastStart DNA Master SYBR Green I reaction mix as previously described [36]. Primers used to detect ␣-synuclein and S29 (housekeeping gene) transcripts were as follows: ␣-synuclein 5Ј-TCCATAGAAGACACCGGG-Ј3; 5Ј-GCT-GAGAAGACCAAAGAGCAA-Ј3; S29 5Ј-AAGGCAAGAT-GGGTCACCAGCAGCTCTA-Ј3 and 5Ј-TACAAAGACTAG-CATGATCGGTTCCACT-Ј3.…”
Section: Rna Isolation and Rt-pcrmentioning
confidence: 99%